Magnetite nanoparticles enhance the bioelectrochemical treatment of municipal sewage by facilitating the syntrophic oxidation of volatile fatty acids. Issue 10 (9th July 2019) - Cruz Viggi, Carolina; Casale, Stefania; Chouchane, Habib; Askri, Refka; Fazi, Stefano; Cherif, Ameur; Zeppilli, Marco; Aulenta, Federico
Abstract: BACKGROUND: Microbial electrochemical technologies (METs) represent a novel platform to harvest the energy trapped in municipal wastewater. At the anode of METs, electro‐active bacteria (EAB) anaerobically oxidize wastewater constituents using the electrode as the terminal electron acceptor and, by so doing, generate an electric current. To convert complex wastewater constituents into electricity, EAB must not only establish syntrophic relationships with other members of the microbial community, but also compete with methanogens for consumption of hydrogen and acetate. Here, we examined the addition of magnetite nanoparticles (NPs) (250 mg Fe L −1 ) as a novel strategy to manipulate such metabolic interactions and in turn maximize the efficiency of wastewater treatment and the yield of electric current generation. RESULTS: Batch experiments carried out either in the presence of a mixture of volatile fatty acids or of a synthetic sewage demonstrated that magnetite addition accelerate the rate of electrogenic oxidation of specific compounds, particularly propionate (up to 120%), an intermediate which frequently accumulates during anaerobic treatment processes, while correspondingly enhancing electric current generation (up to 90%), and diminishing the rate of competing methane generation (up to 50%). Notably, the composition of the microbial community was not substantially affected by the presence of magnetite nanoparticles, possibly suggesting that these latter facilitated extracellular electron transfer mechanisms (among microbes and with the electrode), rather than enriching conditions for specific microorganisms. CONCLUSION: The addition of magnetite NPs may represent a practical strategy to kick‐start a bioelectrochemical system designed for wastewater treatment and improve the effectiveness of electrogenic substrate oxidation processes. © 2019 Society of Chemical Industry